1988
DOI: 10.1007/bf00262893
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine deficiency in the critically ill

Abstract: There have been recent reports of hospitalised patients developing clinical thiamine deficiency, combined with much debate on the optimal supplementation of thiamine for the parenterally fed patient, particularly in the intensive therapy environment. We performed a retrospective study on 158 patients admitted to the Intensive Care Unit who required nutritional support. Patients who survived had significantly higher body thiamine status than those who died (p less than 0.01). There was no difference between ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 19 publications
2
88
0
1
Order By: Relevance
“…(2) Subclinical thiamine deficiency may increase the patient's vulnerability to develop overt signs of thiamine deficiency when confronted with disease and/or chemotherapy associated factors which may superimpose secondary thiamine deficiency, namely: malnutrition, malabsorption, malutilisation, hypophophataemia, hypomagnesaemia, major catabolic and physiological stress,21 and use of various concomitant drugs, for example omeprazole22 and frusemide (furosemide) 23…”
Section: Discussionmentioning
confidence: 99%
“…(2) Subclinical thiamine deficiency may increase the patient's vulnerability to develop overt signs of thiamine deficiency when confronted with disease and/or chemotherapy associated factors which may superimpose secondary thiamine deficiency, namely: malnutrition, malabsorption, malutilisation, hypophophataemia, hypomagnesaemia, major catabolic and physiological stress,21 and use of various concomitant drugs, for example omeprazole22 and frusemide (furosemide) 23…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral vasodilation, biventricular myocardial failure, volume overload, tachycardia, depression of left ventricular function with low ejection fraction, sudden onset cardiac failure and acute renal failure are just some of the signs of wet beriberi [6,63,64]. In contrast, signs of dry beriberi include ophthalmoplegia, ataxia, confusion, memory loss and confabulation in chronic settings [6,65,66].…”
Section: Pathophysiology Related To Tdmentioning
confidence: 99%
“…The prevalence of TD in the ICU, hospitals and the elderly (>76 years of age) has also been examined [15,75,76]. A retrospective study by Cruickshank et al [63] observed a 20% prevalence of TD in intensive care patients requiring nutritional support. A mortality rate of 72% was seen in patients with TD compared to 50% in the non-TD group from 158 patients.…”
Section: Pathophysiology Related To Tdmentioning
confidence: 99%
“…In a retrospective study in critically ill adults in which laboratory biochemical values for thiamine and riboflavin were plotted against prognosis, patients who evolved to death had a higher incidence of low concentrations of these vitamins than did survivors. None of the patients studied presented any clinical signs of vitamin deficiency (4).…”
Section: Introductionmentioning
confidence: 98%